Practice of breast self-examination and associated factors among female health professionals working in public hospitals of Harari regional state: Eastern Ethiopia multicenter study - Dechasa, Deribe Bekele; Asfaw, Henock; Abdisa, Lemesa; Dessie, Yadeta; Bete, Tilahun; Sertsu, Addisu; Hiko, Ahmed; Balcha, Teganu; Eyeberu, Addis; Nigussie, Kabtamu; Tamiru, Dawit (Frontiers in Oncology, 2022)
Breast cancer is the most frequent malignancy among women in both developed and developing countries. Early detection of breast cancer using breast self-examination plays a substantial role in reducing its morbidity and mortality. Despite improved availability of health information the morbidity and mortality caused by breast cancer among females were increasing from time to time and there is no information regarding the practice of breast self-examination in our study area. Objective: This study was aimed at assessing breast self-examination practice and associated factors among female health professionals who were working in public hospitals of Harari Regional State in 2022. Methods: Institutional-based quantitative cross-sectional study design was used to assess the practice of breast self-examination and associated factors among female health professionals who have been working in a public hospital in Harari regional state from March 25 to April 05, 2022. The study subjects were selected using a simple random sampling technique and data were collected by a self-administered and structured questionnaire. The collected data was edited, cleaned, coded, and entered into Epi-Data version 3.1 software and analyzed using the statistical package for social science software version 20. Bivariable and multivariable logistic regression analysis was carried out to see the association between independent and dependent variables. Variable with P-value less than 0.05 at final model were regarded as statistically significant. Result: Among a total of 362 female health professionals, 171 (47.2%) respondents were ever practiced breast self-examination, 229(63.3%) had good knowledge of breast self-examination and 252(69.6%) had a favorable attitude toward breast self-examination. Work experience of ≥5 year (AOR = 2.51; 95% CI: 1.31–4.82), educational status of degree and above (AOR = 7.2; 95% CI: 3.82–10.58), good knowledge about breast self-examination (AOR = 3.4; 95% CI: 1.41–5.40) and favorable attitude toward breast self-examination (AOR = 3.1; 95% CI: 2.11–4.10) were significantly associated with breast self-examination practice. Conclusion: The finding of this study implies the practice of breast self-examination among female health professionals is low. Work experience of ≥5 year, educational status of degree and above, having a good knowledge and favorable attitude toward breast self-examination were significantly associated with breast self-examination.